Performance of an influenza rapid test in children in a primary healthcare setting in Nicaragua. - Aubree Gordon; Elsa Videa; Saira Saborio; Roger López; Guillermina Kuan; Arthur Reingold; Angel Balmaseda; Eva Harris (PLoS ONE, 2009)
BACKGROUND: Influenza is major public health threat worldwide, yet the diagnostic accuracy of rapid tests in developing country settings is not well described. METHODOLOGY/PRINCIPAL FINDINGS: To investigate the diagnostic accuracy of the QuickVue Influenza A+B test in a primary care setting in a developing country, we performed a prospective study of diagnostic accuracy of the QuickVue Influenza A+B test in comparison to reverse transcriptase-polymerase chain reaction (RT-PCR) in a primary healthcare setting in children aged 2 to 12 years in Managua, Nicaragua. The sensitivity and specificity of the QuickVue test compared to RT-PCR were 68.5% (95% CI 63.4, 73.3) and 98.1% (95% CI 96.9, 98.9), respectively, for children with a fever or history of a fever and cough and/or sore throat. Test performance was found to be lower on the first day that symptoms developed in comparison to test performance on days two or three of illness. CONCLUSIONS/SIGNIFICANCE: Our study found that the QuickVue Influenza A+B test performed as well in a developing country primary healthcare facility setting as in developed country settings.